ANALISIS KOMODITI UNGGULAN SUBSEKTOR TANAMAN PERKEBUNAN DI KABUPATEN KEPULAUAN MENTAWAI - Suryani, Nova (PT. Media Akademik Publisher, 2024)
The agricultural sector is the largest contributor to the regional income in the Mentawai Islands Regency. Plantations play a crucial role in the development of the agricultural sector at both the national and regional levels. Therefore, research is needed to determine the commodity subsector of plantations that serves as the leading commodity in the Mentawai Islands Regency. The results of this research are expected to provide guidance on the direction of development in the Mentawai Islands Regency, enabling it to focus on leading commodities that can maximize prosperity for the local community. The methods employed include Location Quotient (LQ) analysis and shift-share analysis. Based on the LQ analysis, it is found that the key commodities in the Mentawai Islands Regency are coconut, cloves, nutmeg, and patchouli. According to the shift-share analysis, the second-priority commodity subsector in plantation crops in the Mentawai Islands Regency includes coconut, cocoa, and rubber. The third-priority commodity subsector in plantation crops in the Mentawai Islands Regency includes cloves, nutmeg, candlenut, cinnamon, patchouli, and betel